The Influence of Business Location, Price, and Consumer Satisfaction on Buying Interest in Stores: Pengaruh Lokasi Usaha, Harga, dan Kepuasan Konsumen Terhadap Minat Beli di Toko - Andani, Retno; Oetarjo, Mas (Universitas Muhammadiyah Sidoarjo, 2022)
In an effort to bring in new customers and also retain customers, it requires high buying interest from consumers who ultimately make purchasing decisions. There are several factors that must be considered by entrepreneurs in starting a business, namely to coincide with the selection of location, price, and consumer satisfaction. To find out that the location of the business affects the interest in buying in Pak Tris 5758 Stores. This research uses quantitative methods. Sampling in this study used incidental sampling methods in consumers of Pak Tris 5758 Stores, namely consumers who shop at Pak Tris 5758 Stores, with a total of 96 respondents. The data collection technique used is to use kuesioner. The data analysis technique in this study uses multiple linear regression through the SPSS Statistic program version 22. The results showed that Business Location (X1), Price (X2), and Consumer Satisfaction (X3) simultaneously affect Buying Interest (Y) in Pak Tris 5758 Stores. Business Location (X1) partially affects Buying Interest (Y), Price (X2) partially affects Buying Interest (Y) and Consumer Satisfaction (X3) partially affects Buying Interest (Y).